Desarrollo sostenible en las empresas del Perú: ¿voluntario u obligatorio? - Ruiz Vásquez, Úrsula Patricia (2023)
The objective of this article is to determine whether compliance with the concept of sustainable development, by companies in Peru, is voluntary or mandatory, based on a detailed review of literature related to corporate social responsibility, sustainability reports or reports, companies. with B certification and BIC society; as well as the analysis of various rulings of the Constitutional Court about some of these concepts and our social market economy regime. Based on the results of the aforementioned analysis, it will be possible to determine that Peruvian companies, in addition to generating economic profitability, need to incorporate social and environmental components into their management, through absolutely measurable, verifiable and sustainable actions that contribute to present and future generations of the country can enjoy a dignified life.